Continuous Software Engineering of a Cloud-Native Application - Mamani Rodriguez, Zoraida (2024)
A cloud-native application is a software specifically designed to run in the cloud, focusing on distributed, elastic, horizontally scaled, and microservice-based architecture with autonomous deployment. These applications are designed with cloud-native web architectures, operate on an elastic self-service platform, and stand out because of their resilience and elasticity. Continuous software engineering integrates requirements engineering, development, and operations in a continuous loop with reciprocal feedback to produce quality software. The present work proposes to design and implement a cloud-native application applied to the SIGCON case study from a continuous software engineering perspective. It uses the CaaS cloud service model, applies the BFF pattern in software construction, containerizes the frontend, backend, and storage, and presents the results.